Adopting the National Coaching Standards in Sport Programs. (20th January 2021) - Heidorn, Brent; Stoepker, Peter
Abstract : This article briefly highlights each overarching theme and provides insight for ways coaches can apply these standards while working with athletes in various sport environments. Coaches play a very important role in an athlete's life. In many cases, this role continues far beyond one sport season. Therefore, it is imperative for all coaches to be cognizant of the nationally adopted standards of the profession, but more importantly, consistently apply them.